Somaterapia e contracultura: criação e desenvolvimento de uma técnica terapêutica no Brasil dos anos 1970 - Ferraz, Giovan Sehn (2018)
This work, developed along the research line Culture, Migrations and Work of the Postgraduate Program in History at the Universidade Federal de Santa Maria (PPGH-UFSM), counting with assistance of CAPES/DS, aims to understand how a therapeutic technique with anarchist and scientific pretension, Roberto Freire's Somaterapia, arose and developed from the scenario of the Brazilian and international counterculture of the 1960s to the 1980s. Somaterapia, or just Soma, was idealized and developed by Roberto Freire from experiences inside the Centro de Estudos Macunaíma, where they researched techniques of unlocking creativity for actors. According to its idealizer, the therapy was born from his personal contact with the theatrical technique of an American theater group, the Living Theater, in its show Paradise Now, whose technique was based on the theories of Wilhelm Reich. Somaterapia, according to Freire and his followers, seeks to free the individual from neurosis and muscle harnesses caused by the repressive society through body dynamics, theater plays and Capoeira Angola. It was chosen to analyze this object in relation to the phenomenon of the Counterculture because of the verified connections and approaches, understanding the object as emergent from this phenomenon. Freire's bibliographical work was the main source of the research, but it was also analyzed: academic productions and electronic sites of somatherapists and sympathizers; editions of the Jornal Tesão and Boletim Brancaleone, linked to Somaterapia; and materials, announcements and references in the digital collection of the Folha de São Paulo newspaper and some other press vehicles. In the analysis of the sources, based on the methodological choices that were mad and under the bias of the theoretical reference used, it was ascertained the recurrence of memorialist discourses about Freire's life trajectory and the history of Somaterapia, constituted by an effort of ordering the past in which a coherent and rational narrative was presented. However, at the intersection of sources and information, there were several incongruities and dissent, which were interpreted as reflections of stories that were probably given in a much more complex, fluid and even contradictory way, as it is understood to be proper to human processes.